Free volume structure of realgar α-As4S4 by positron annihilation lifetime spectroscopy. (April 2015) - Shpotyuk, O.; Ingram, A.; Demchenko, P.
Abstract: Atomic-deficient free volume structure of realgar α-As4S4, the low-temperature modification, of tetraarsenic tetrasulfide polymorphs, is studied using positron annihilation lifetime spectroscopy. Eventual channels of positron annihilation in this molecular crystal are shown to be connected with low electron density entities around cage As4S4 molecules composing realgar-type structure of monoclinic P21/n space group. The overlapped spaces of bond-free solid angles around S atoms forming self-closed As4S4 molecules contribute preferentially to positron trapping modes, while a competitive influence of bound positron–electron states (positronium) stabilized in intermolecular spaces occurs also to be essential in the decomposed lifetime spectra too. Highlights: Positron annihilation in realgar occurs due to mixed positron–positronium trapping. Overlapped S-related volumes composing cage As4 S4 molecule act as trapping defects. Subnanometer voids of ~80 Å 3 volume are responsible for positron trapping in α-As4 S4 . The value of 0.224 ns corresponds to defect-free bulk positron lifetime in realgar.